Sistem Pembinaan Renang Anak Usia Dini di Klub Renang Se-Kabupaten Magelang - Dewi, Martiana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The aim of this study is to know the implementation of early childhood swimming coaching in Magelang regency swimming club in 2014. The research method in this study was descriptive qualitative method. There were some evidences which were used to support the data, they were plaque, photos, management structure and others. The research findings shows that: (1) the development which was undertaken including coaching recruitment, coaching quarantine, and achievement quarantine which were still poor, (2) the coaching program which are carried out that is still poor, because most of the clubs in the district of Magelang just doing daily coaching program, (3) infrastructure is still poor (4) the management of the organization has not gone well because not all swimming club organizations in Magelang District has many elements such as the base budgeting, household budgeting, work plans and budgets, (5) not all the coaches in the Magelang District swimming clubs has coaching certificates, (6) the athletes are able to achieve in the local level but, in the national level has not been available yet. Finally, it can be concluded that the implementation of the early childhood swimming coaching system in the Magelang District swimming clubs has not run well yet.